2DToonShade: A stroke based toon shading system. Issue 1 (June 2019) - Hudon, Matis; Grogan, Mairéad; Pagés, Rafael; Ondřej, Jan; Smolić, Aljoša
Highlights: A semi-automatic method for creating shades and self-shadows in cel animation. Tool designed to stay as close as possible to the natural 2D creative environment and therefore provides an intuitive and user-friendly interface. Shade enhancement system allowing the deformation of shades around detail strokes, such as, but not limited to, facial elements or cloth folds. An efficient and robust propagation technique allowing the reduction of the effort required to create plausible shades and local self-shadows in a hand-drawn animation. Graphical abstract: Abstract: We present 2DToonShade: a semi-automatic method for creating shades and self-shadows in cel animation. Besides producing attractive images, shades and shadows provide important visual cues about depth, shapes, movement and lighting of the scene. In conventional cel animation, shades and shadows are drawn by hand. As opposed to previous approaches, this method does not rely on a complex 3D reconstruction of the scene: its key advantages are simplicity and ease of use. The tool was designed to stay as close as possible to the natural 2D creative environment and therefore provides an intuitive and user-friendly interface. Our system creates shading based on hand-drawn objects or characters, given very limited guidance from the user. The method employs simple yet very efficient algorithms to create shading directly out of drawn strokes. We evaluate our system through a subjective user study and provide qualitative comparison of our method versus existing professional tools and recent state of the art.